1984
DOI: 10.1007/bf01742297
|View full text |Cite
|
Sign up to set email alerts
|

General and selective inhibition of pancreatic enzyme discharge using a proteinase inhibitor (FOY-305)

Abstract: The guanidino acid esters (FOY, FOY-305) represent a new class of potent proteinase inhibitors and are thought to have a beneficial effect on the course of acute pancreatitis. Because of their structure and low molecular size they might enter cells and interfere with cellular processes. To test this possibility in the case of the exocrine pancreas a series of in vivo and in vitro studies was carried out to analyse intracellular transport and discharge of pancreatic enzymes in the presence of FOY-305. The infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In addition to these indi rect effects observed also after feeding with soybean trypsin inhibitor or aprotinin. direct effects of camostate on the pancreas could be expected, because this small molecular weight substance may affect intracellular pro cesses [1]. Furthermore, camostate is known to inhibit phospholipase A2 (PLA2) activity in vitro [7,21], and this enzyme has recently been shown to influence insulin secretion [24], The aim of this study was to investigate the short-term and long-term effects of ca mostate on the endocrine pancreas of the rat.…”
mentioning
confidence: 99%
“…In addition to these indi rect effects observed also after feeding with soybean trypsin inhibitor or aprotinin. direct effects of camostate on the pancreas could be expected, because this small molecular weight substance may affect intracellular pro cesses [1]. Furthermore, camostate is known to inhibit phospholipase A2 (PLA2) activity in vitro [7,21], and this enzyme has recently been shown to influence insulin secretion [24], The aim of this study was to investigate the short-term and long-term effects of ca mostate on the endocrine pancreas of the rat.…”
mentioning
confidence: 99%
“…A similar effect was demonstrated for gabexate mesilate, a closely related compound, on basal and cerulein-stimulated pancreatic protein secretion [5]. However, whereas Adler et al [1] presented evidence for an interference of camostate with the intracellular transport and discharge of newly synthesized enzymes from pancreatic lobules in vitro, St6ckmann et al [11] reported no effect of the proteinase inhibitor on the CCK-stimulated enzyme release from rat pancreatic lobules. In the case of gabexate mesilate, Keim and G6ke [5] were unable to demonstrate an influence of i.v.…”
mentioning
confidence: 71%
“…It remains an open question why i.v. infusion of camostate leads to a short lasting but nevertheless pronounced inhibition of protein and enzyme discharge from the cannulated pancreatic duct under both basal and stimulated conditions [1]. Previously, this transient inhibitory effect was ascribed to a possible interference of the proteinase inhibitor with the overal discharge process which involves hormones, membrane receptors, intracellular second messengers, and membrane recogni-tion and fusions events during exocytosis [1].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ability of FOY to enter the acinar cell is a disadvantage in that the drug might sustain the exocytosis blockade [25, 26], and hence the drive to inflammation (fig. 1).…”
Section: The Time Factormentioning
confidence: 99%